2022
DOI: 10.1002/ppul.26203
|View full text |Cite
|
Sign up to set email alerts
|

Foreign body aspiration in Israeli children during the COVID‐19 pandemic

Abstract: Background: Since the outbreak of the coronavirus disease 2019 pandemic, there has been a decline in pediatric emergency department visits. Our aim was to assess the pattern of pediatric foreign body aspiration (FBA) during the first year of the COVID-19 pandemic, in comparison to the prior years. Methods:In this retrospective multicenter study, we compared the number of children who presented with FBA during the COVID-19 year (March 1, 2020 to February 28, 2021) to the annual average of the years 2016-2019. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Despite the hypothesis that isolation policies and home-office movement can be additional risk factors for FBI and FBA [9], our study showed no major changes in the demographic profile of patients admitted for FB and no major impact of COVID-19 on the presented subject [10]. Because most of the authors agreed on the in- creasing trend in foreign body diagnoses, there are some suggesting that better parental supervision could lead to improvement in that field [10,11]. There is limited literature in the topic of foreign bodies in children during COVID-19.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Despite the hypothesis that isolation policies and home-office movement can be additional risk factors for FBI and FBA [9], our study showed no major changes in the demographic profile of patients admitted for FB and no major impact of COVID-19 on the presented subject [10]. Because most of the authors agreed on the in- creasing trend in foreign body diagnoses, there are some suggesting that better parental supervision could lead to improvement in that field [10,11]. There is limited literature in the topic of foreign bodies in children during COVID-19.…”
Section: Discussioncontrasting
confidence: 86%
“…There is limited literature in the topic of foreign bodies in children during COVID-19. As we presented a history of 236 children, most of the studies contributed less than 100 patients [10,12,13], some of them being case reports [14, 15] and others using national electronic databases [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is why the incidence of FBA is significantly higher in countries where peanuts and seeds are traditionally eaten at an early age than in countries where these foods are introduced much later [14 ▪▪ ]. Interestingly, there were fewer cases of FBA during COVID-19 lockdown periods, compared to postlockdown periods, presumably due to better parental supervision [15 ▪ ].…”
Section: Prevalence and Incidence Of Foreign Bodies Aspirationmentioning
confidence: 99%